On demand caesarean section: What’s women’s attitude? - Shrestha, Nira S; Pradhan, Sumita (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Objectives: To evaluate the knowledge and attitude of Nepalese women towards mode of delivery and caesarean on demand. Study design: Hospital based cross sectional descriptive study where 200 pregnant women after 37 completed weeks of gestation were recruited randomly and interviewed, and their answers were analyzed. Results: Of the 200 interviewed pregnant women, all of them knew about normal vaginal delivery and caesarean delivery, but only 30% knew about instrumentally assisted delivery and 9% had heard about painless labour. Vaginal delivery was the preferred mode in 93% and 7% preferred caesarean delivery. Only 35% of the interviewed women believed that women should have the right to demand a caesarean section Conclusion: Knowledge assessment of two hundred women regarding the mode of delivery clearly indicates the need for strengthening counseling aspect of antenatal care and awareness program regarding mode of delivery. In Nepal on demand caesarean section is not provided in the University Teaching Hospital. However one third of women still felt that women should have the right to choose caesarean section on demand. Key words: Attitude, mode of delivery, Caesarean on demand. doi:10.3126/njog.v2i2.1448 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 12 - 15